Somatostatin Receptor Type 2–Based Reporter Expression after Plasmid-Based in Vivo Gene Delivery to Non–Small Cell Lung Cancer - Lin Han; Murali Ravoori; Guanglin Wu; Ryo Sakai; Shaoyu Yan; Sheela Singh; Kai Xu; Jack A. Roth; Lin Ji; Vikas Kundra (Molecular Imaging)
Plasmids tend to have much lower expression than viruses. Gene expression after systemic administration of plasmid vectors has not been assessed using somatostatin receptor type 2 ( SSTR2 )-based reporters. The purpose of this work was to identify gene expression in non–small cell lung cancer (NSCLC) after systemic liposomal nanoparticle delivery of plasmid containing SSTR2-based reporter gene. In vitro, Western blotting was performed after transient transfection with the plasmid cytomegalovirus (CMV)-SSTR2, CMV-TUSC2-IRES-SSTR2, or CMV-TUSC2. SSTR2 is the reporter gene, and TUSC2 is a therapeutic gene. Mice with A549 NSCLC lung tumors were injected intravenously with CMV-SSTR2, CMV-TUSC2-IRES-SSTR2, or CMV-TUSC2 plasmids in DOTAP:cholesterolliposomal nanoparticles. Two days later, mice were injected intravenously with 111 In-octreotide. The next day, biodistribution was performed. The experiment was repeated including single-photon emission computed tomography/computed tomography (SPECT/CT). Immunohistochemistry was performed. In vitro, SSTR2 expression was similar in cells transfected with CMV-SSTR2 or CMV-TUSC2-IRES-SSTR2. TUSC2 expression was similar in cells transfected with CMV-TUSC2 or CMV-TUSC2-SSTR2. Biodistribution demonstrated significantly greater 111 In-octreotide uptake in tumors from mice injected with CMV-TUSC2-IRES-SSTR2 or CMV-SSTR2 than the control plasmid, CMV-TUSC2 ( p < .05). Gamma-camera and SPECT/CT imaging illustrated SSTR2 expression in tumors in mice injected with CMV-TUSC2-IRES-SSTR2 or CMV-SSTR2 versus background with control plasmid. Immunohistochemistry corresponded with imaging. SSTR2-based reporter imaging can visualize gene expression in lung tumors after systemic liposomal nanoparticle delivery of plasmid containing SSTR2-based reporter gene or SSTR2 linked to a second therapeutic gene, such as TUSC2 .